Affect, empathy, and engagement: Reading African conflict in the global literary marketplace. (June 2017) - Krishnan, Madhu
This article considers the intersection of ethics, responsibility, and literature through readings of Aminatta Forna's The Memory of Love and Dave Eggers' What Is the What . Examining the ways in which each novel situates its staging of African conflict against the a priori image of Africa, the article focuses on the ways in which each novel demands a readerly engagement based on alterity. Rather than viewing the text as a passive repository of ethical lessons, the article suggests that by leveraging narrative unreliability both novels create a vision of literature as the active site of ethical engagement and conflict.